Online Marketplace Operators’ Civil Liability for Third Party Infringements of Trademark Rights - Drakšas, Justinas (Teisė, 2024)
This paper presents an analysis of the possibility of civil liability application for operators of online marketplaces for third party trademark infringements in Lithuania. In order to meet the objectives of the work, the author analyses the concept of trademark use, reviews the recent case law of the Court of Justice of the European Union on the qualification of individual cases of trademark use, and discusses the positions on the requirements for online marketplaces with regard to content control and application of ‘safe harbours’. The paper concludes that, although the possibility of ‘traditional’ indirect civil liability for infringements of trademark rights is not currently provided for in Lithuanian law, the alternative measures that are already established, such as direct civil liability for unauthorised trademark use, or civil liability for breach of the general duty of care, suggest that the current model of civil liability for online marketplaces is sufficient.
Keywords: civil liability for third-party infringements; online marketplaces; internet intermediaries; use of trademarks; safe harbours